The ERK-1 function is required for HSV-1-mediated G1/S progression in HEP-2 cells and contributes to virus growth - Colao I; Pennisi R; Venuti A; Nygårdas M; Heikkilä O; Hukkanen V; Sciortino MT (NATURE PUBLISHING GROUP, 2022)
The herpes simplex virus 1 is able to readdress different cellular pathways including cell cycle to facilitate its replication and spread. During infection, the progression of the cell cycle from G1 to S phase makes the cellular replication machinery accessible to viral DNA replication. In this work we established that HSV-1, in asynchronized HEp-2 cells, strictly controls cell cycle progression increasing S-phase population from 9 hours post infection until the end of HSV-1 replication. The G1/S phases progression depends on two important proteins, cyclin E and CDK2. We demonstrate that their phosphorylated status and then their activity during the infection is strongly correlated to viral replication events. In addition, HSV-1 is able to recruit and distribute ERK1/2 proteins in a spatio-temporal fashion, highlighting its downstream regulatory effects on cellular processes. According with this data, using chemical inhibitor U0126 and ERK dominant negative cells we found that the lack of ERK1 activity affects cyclin E protein accumulation, viral gene transcription and percentage of the cells in S phase, during the viral replication. These data suggested a complex interaction between ERK, cell cycle progression and HSV-1 replication.